Health Literacy and New Normal in Older Adults - Chaoayachai, Wanrudee; Prompahakul, Ruttikarn; Prasertsang, Areeya (Journal of The Royal Thai Army Nurses, 2021)
Health literacy is a crucial factor that can lead a person to appropriate health behaviors, decrease risk of health problems, and is necessary to be continuously developed. Especially in the new normal era, which includes the improving of online social networking and technological skills are important to enhance one’s health literacy. The development of health literacy in older adults is limited due to functional decline; hearing and vision loss; learning and memory problems, including chronic illness and health care cost. These factors are barriers to access and utilize technology for older adults. This academic article aimed to review the evidence of health literacy and new normal lifestyle among older adults in order to understand and guide further study. Moreover, this can be applied in nursing practice for improving health care and quality of life in older adults.